EXPLORING CHALLENGES OF INDONESIAN EFL TEACHERS IN ADOPTING TEACHER-RESEARCHER IDENTITY THROUGH CLASSROOM ACTION RESEARCH - Prabandari, Carla Sih; Badiozaman, Ida Fatimawati Adi; Turner, Kristina (LLT Journal: A Journal on Language and Language Teaching, 2024)
This study centres on investigating the challenges faced by Indonesian EFL teachers when conducting classroom action research (CAR). In this pursuit, the paper employs content analysis techniques to delve into teachers’ competency in conducting CAR. This exploration is facilitated through an in-depth examination of the teachers’ CAR reports and conversations in the discussion forum on the learning management system (LMS) of Pendidikan Profesi Guru (PPG) or the Teacher Professional Education (TPE) program. The thematic content analysis was conducted manually and using NVivo 12 software to ease the data coding process. The results of the study showed that teachers’ knowledge of CAR varied, with most teachers perceiving an improvement in students’ scores as the primary indicator of CAR success. It also found that some teachers grappled with the technical aspects of conducting CAR, such as formulating appropriate research questions, reviewing the literature, selecting appropriate research instruments, analysing data, and reporting writing, while others encountered practical obstacles, including constraints related to time and resources. This study underscores the importance of providing ongoing support for EFL teachers to develop their CAR competencies and ultimately improve their teaching practices. The paper concludes with implications for future research and practice.